Pregnant Women's Depression and Mental Health Knowledge - Latifah Lutfatul; Setiawati Nina; Kartikasari Aprilia; Amalia Reza Fajar; Susmarini Dian (E3S Web of Conferences)
Understanding maternal mental health is crucial for the prevention and management of antenatal depression. This study aimed to determine the level of mental health knowledge of pregnant women who experienced depressive symptoms. A cross-sectional study of 175 pregnant women, each with Edinburgh Postnatal Depression Scale (EPDS) scores ≥ 11, was collected using non-probability sampling techniques. Mental health knowledge was evaluated using the Mental Health Knowledge Scale (MHKS). Univariate and bivariate analyses determined the association among knowledge, antenatal depression, and participants' characteristics. The mean score of the MHKS was 14.08 out of 20 points (70.4%), and the standard deviation was 3.26. Spearman correlation analysis revealed a statistically significant association between the total knowledge score and the depression score (r=0.221, p=0.003). A Kruskal Wallis test indicated a relationship between the depression score and type of family (p=0.016), concerns about the cost of childbirth (p=0.005), history of depression (p=0.031), and gestational age (p=0.035). These results imply that the women with higher mental health knowledge were more likely to have higher EPDS scores. In conclusion, the findings indicate that women’s knowledge levels exhibit substantial variability. The improvement of mental health knowledge among pregnant women is essential for reducing the risk associated with depression.